Distinguishing placenta accreta from placenta previa via maternal plasma levels of sFlt-1 and PLGF and the sFlt-1/PLGF ratio. (24th June 2022) - Zhang, Fengyuan; Gu, Mengqi; Chen, Pengzheng; Wan, Shuting; Zhou, Qian; Lu, Yuan; Li, Lei
Abstract: Introduction: Our study aimed to distinguish patients with placenta accreta (crete, increta, and percreta) from those with placenta previa using maternal plasma levels of soluble fms-like tyrosine kinase-1 (sFlt-1) and placental growth factor (PLGF) and the sFlt-1/PLGF ratio. Methods: We obtained maternal plasma from 185 women in late pregnancy and sorted them into three groups: 72 women with normal placental imaging results (control group), 50 women with placenta previa alone (PP group), and 63 women with placenta previa and placenta accreta (PAS group). The concentrations of sFlt-1 and PLGF in the maternal plasma were measured using ELISA kits and the sFlt-1/PLGF ratio was calculated. Result: The median (min-max) sFlt-1 levels and the sFlt-1/PLGF ratio in the PAS group (12.8 ng/ml, 3.8–34.2 ng/ml) (133, 14-361) were lower than in the PP group (28.7 ng/ml, 13.1–60.3 ng/ml) (621, 156-2013) (p < 0.0001 and P < 0.0001, respectively). The median (min-max) PLGF levels in the PAS group (108 pg/ml, 38-679 pg/ml) was higher than that in the PP group (43 pg/ml, 12-111 pg/ml) (p < 0.0001 and p < 0.0001, respectively). The area under the ROC of the sFlt-1 levels, PLGF levels, and sFlt-1/PLGF ratio were 0.91, 0.90, and 0.99, respectively; the cut-off values were 18.9 ng/ml, 75.9 pg/ml, and 229.5, respectively. The concentration of sFlt-1 and sFlt-1/PLGF ratio were associated with the volume of blood loss (-.288*, -.301*). Discussion: The concentrations of sFlt-1 and PLGF and ratio of plasma sFlt-1/PLGF may distinguish patients with placenta accreta from those with placenta previa. Highlights: These biological markers may distinguish patients with placenta accreta from those with placenta previa. sFlt-1 levels and sFlt-1/PLGF ratio were related to the volume of blood loss. These biological markers may predict placenta accreta.